(untitled) (MUZIKOLOGIJA-MUSICOLOGY, 2024)
The opus of contemporary Serbian composer Milorad Marinković (b. 1976), which encompasses works of choral, chamber, concertante and symphony music, leans towards classical forms of artistic music, Serbian folklore music, and Serbian Orthodox church chant. This paper deals with pieces composed for larger instrumental ensembles: Herojska uvertira (Heroic Overture) for symphony orchestra, Psalmodija (Psalmody) for symphony orchestra, Koncert za klavir i orkestar (Piano concerto) and Mala opera (Little Opera) for chamber ensemble (septet) with prominent soloist parts of ﬂute and clarinet. Special attention is placed on different procedures used by Marinković to accomplish wholeness and integration of the musical tissue. This paper observes these pieces as examples of religious music, having in mind the composer’s own understanding of the notion. Among common characteristics of the observed works that justify this point of view are specifc single movement forms and the prominent role of main thematic materials, a cyclic principle, and programmatic elements. References to Serbian church chant observed in Marinković’s instrumental works are also discussed, especially in parallel with the analogue procedures used by Ljubica Marić (1909– 2003), one of the composer’s role models. Although Marinković’s works for instrumental ensembles do not fall into the category of spiritual music in its narrow sense (as defned by the composer himself), in this paper they are nevertheless considered as “spiritual” in a broader sense, as an expression of the composer’s desire to spiritualize his entire artistic output.